A comparative study of the economic ideas of Ibn Taymiyyah and Ibn Khaldun and its relevance to conventional economic thought - Abdelhakim, Nedjah (Kulliyyah of Economics and Management Sciences, International Islamic University Malaysia, 2000)
The thrust of this study is to draw a parallel between the economic ideas of Ibn Taymiyyah and Ibn Khaldun then demonstrate the originality and relevance of their contribution to modern economic thought. To this end we have prefaced this problematic research with a number of vexed questions: why do Muslim scholars in general react differently for the same stimuli? Why do they apply different methodological approaches though they emerge from the same background as shown - as a sample - in the study of Ibn Taymiyyah and Ibn Khaldun? Is our ample intellectual and jurisprudential legacy mainly confined to linguistic efforts and legalistic approaches? What is most striking and significant in the economic contributions of Ibn Tymiyyah and Ibn Khaldun? and all alike. Attempting these questions has evoked the major part of this research. This study abides by two stages methodology, namely, historical methodology and analytical comparative methodology. The former is necessitated by the sheer importance of tracing the general historical setting ( environment) that inevitably influences any sort of scholarship. As for the latter method is to depict the focal demarcations between Ibn Taymiyyah and Ibn Khaldun's economic thought by following certain theoretical parameters. The major findings of his study show that the space-time factor along with educational background, family descent, personal character, job's experience, all have significant bearing in directing the intellectual products of both scholars under study. As a matter of fact, Ibn Taymiyyah concurs with Ibn Khaldun on a number of issues such as free play of market, functions of money, taxation, etc. However, there exist conspicuous discrepancies on other economic aspects that differ significantly between these two scholars, particularly, their method of inquiry and their views on the role of state in the economy and also the process of distribution and other related issues. Moreover, it has been attested in this research that both scholars were original thinkers and system builders and notwithstanding the lapses of centuries, their contribution still keeps up its vigour, relevance and modernity. For Ibn Taymiyyah his ideas of "just price" (competitive price), basic needs, self sufficiency and currency debasement make him in par with many modern economists who came after him few centuries ahead. As for Ibn Khaldun, his many insightful economic discussions like those elaborated on labour theory of value, taxation and economic growth has not only testify to his geniality but also to unquestionably accredit him with the title of being "the founding father of economics"